Spatial Distribution of Poverty in Chile - Agostini, Claudio (Estudios de Economía, 2016)
Chile’s recent success in reducing poverty has been remarkable, with poverty rates falling by approximately two-thirds over the last 20 years. However, further gains against poverty may be inhibited by the increasing difficulty associated with targeting fewer poor people and better, more localized information may thus be required. Moreover, public policy that seeks to understand the relationship between poverty, socioeconomic status and urban or rural residence depends on survey data that may not be representative at low levels of aggregation; although censuses are representative by definition, they generally lack detailed income data. Recent mapping techniques combining census and survey data afford detailed descriptions of the spatial distribution of poverty. Indeed, such techniques enable the calculation of robust and statistically precise estimates of poverty at low levels of aggregation, allowing a more nuanced picture of poverty to emerge. In this paper we use such methodologies to produce consistent estimates of both rural and urban poverty at the county level in Chile. The results demonstrate considerable heterogeneity in local poverty, suggesting that future antipoverty policies must be targeted at the local level. Moreover, the estimates we provide may be used to further analyze the causes and consequences of localized poverty.